P48 Implantable loop recorders: The search for perfect patient selection. (2nd March 2016) - Howell, Alison J; Stuart, Graham; Walsh, Mark
Abstract : Introduction: Implantable Loop Recorders (ILR) permit long term electrocardiographic monitoring allowing symptom-rhythm correlation in children who are suspected to have an arrhythmia. We reviewed the presenting complaint and previous investigations in order to aid patient selection for the ILR. Method: We conducted a retrospective review identifying patients 16 years and younger with structurally normal hearts undergoing ILR implantation in Bristol Children's Hospital through the Heartsuite database over a 10 year period from 2004 – 2014. Statistical analysis was performed with the Fishers exact probability test. Results: One hundred children were identified. Mean age was 11.0 years (range 1.2 – 16.9 years) with a male: female ratio of 1.2:1. The predominating complaint was syncope in 62.7%, palpitations in 32.5% and dizziness in 4.8%. Eighty-three of the 100 children had explantation data (8 patients had follow-up out of region, 9 ILR remained in situ ) with 79 having a documented ECG/Holter prior to ILR. Overall 24/79 (30%) of patients required intervention following ILR implantation, either permanent pacemaker (PPM) (n = 7), medication or ablation (n = 17). There was a significantly higher number of patients requiring intervention post ILR if the prior ECG/Holter was abnormal (Table 1 ). Fifty percent (13/26) of patients presenting with palpitations required further intervention for an arrhythmia identified on the ILR compared with 20% (10/49) of those presenting with syncope (p = 00.01). Of those presenting with syncope, a PPM was required in 5/22 (23%) with an abnormal ECG/Holter compared with 2/27 (7%) with a normal ECG/Holter (p = 00.2). None of the children presenting with palpitations or dizziness required PPM placement. Use of event recorders was low (6/79, 7.6%). Incidence of complication was 5% with 2 infections (1 requiring removal of the ILR, 1 treatment with antibiotics), 1 hypertrophic scar and 1 re-implanted due to discomfort. Conclusions: Presenting complaint does seem to influence the outcome following ILR implantation. The need for further intervention following ILR implantation was more likely if children present with an abnormal ECG/Holter monitor. Therefore longer-term non-invasive monitoring could be justified in those with normal ECG/Holter monitoring rather than using ILR's. Further prospective study and protocol development is warranted in order to establish the perfect patient selection.